ENHANCHING STUDENT ACHIEVEMENT AND MOTIVATION: THE DEVELOPMENT OF CHILDREN LEARNING IN SCIENCE MODEL-BASED TREE MEDIA - Wahyuni Fajar Arum (JURNAL PENA SAINS, 2018)
This research aims to find the effect the research and development of voiced tree media based on Children Learning in Science (CLIS) model of learning achievement and learning motivation of SDN 1 and 2 Ngembel students. The research model in this research is Research and Development. The approach in this research uses models from Borg and Gall. This research combines the voiced tree media with CLIS model. Data collection techniques in this study were carried out by the literature study, observation, and the implementation of the pre-test and post-test conducted at the beginning and end of the learning process. Based on the results of research and data, it was concluded that the application of voiced tree media was based on the CLIS model influences students' learning achievement in physics, both SDN 1 Ngembel and SDN 2 Ngembel. SDN 1 Ngembel produces a value of t table of 2.160369 while t count for -15.064, while SDN 2 is released for ttable is 2.160369 while tcount is for -14.408. The development of voiced tree media based on CLIS model also influences students' learning motivation with the results of mean data from observations of learning when learning the process at SDN 1 learning is 15.14 motivations when the learning process takes place at SDN 2 learning is 14.4.